Technological innovation in China : - Simon, Denis Fred (Ballinger Pub., 1988)
One of the major barriers to industrial innovation in China has been the presence of multiple vertical bureaucratic barriers that have inhibited greater functionally oriented horizontal coordination and cooperation. This has proven to be a major problem in the case of on-going efforts to promote new, technologically dynamic industries such as microelectronics in China. Through a case study of technological innovation in Shanghai's semiconductor industry, the authors show how these vertical barriers have affected the innovation process and how recent economic and S&T reforms are designed to correct some of the existing innovation bottlenecks. They suggest that developments in Shanghai manifest the evolution of a two-pronged strategy for development of electronics in China, where significant elements of both planning and the market are being combined to close the technological gap between the People's Republic of China and the West by the onset of the twenty-first century